Posted by **Miley** on Friday, December 27, 2013 at 9:29am.

f(x)=7x^3+13x^3-3x^2. Find f(-6)

Also how do you solve this kind of question

- Math -
**Reiny**, Friday, December 27, 2013 at 10:24am
notice that in the place of x in f(x) you now find a -6

so in the expression , replace x with -6 as well

f(x) = 7x^3+13x^3-3x^2

f(-6) = 7(-6)^3 + 13(-6)^3 - 3(-6)^2

= ...

I suspect a typo, why would you have two different cubic terms ?

- Math -
**Miley**, Friday, December 27, 2013 at 4:00pm
So for this kind of question. You just replace the variables right?

## Answer this Question

## Related Questions

- Algebra - Hello all - I would like to check my work on 2 problems. Solve by ...
- Algebra - Can you pleas Solve the quadric equation step by step 4x square =13x+...
- intermidate alegbra - Solve each equadratic equation by factoring. 6^2-13x-28 36...
- Math - I know that I posted this already but my question has not been answered...
- math/algebra - subtract. express in simplest form 13x/30 - 4x/ 15 = factor the ...
- Math - Solve the following equation. 4.7 = 1.13x^2 Do i square root the 1.13x^2 ...
- Math - My work on simplifying this function: g(x)=(-3x^2-13x-13) g(x)=-3x^2-13x-...
- math - can someone show me the steps for this problem because i got it incorrect...
- *** Discrete Math *** - I would like to know if my answers are correct. I also ...
- intermidate algebra - 6^2-13x=-5 6^2-13x=-5 6^2=13x-5 I have tried this problem ...